1616 Antibiotic Use in The Management of Mandibular Fractures: A Survey of Current Practice in the UK. (12th October 2021) - Kumar, D; Kent, S; Dawoud, B; Kysas, P
Abstract: Aim: Traumatic mandibular fractures account for a significant proportion of UK oral and maxillofacial trauma. Prophylactic antibiotics is standard practice for management of these patients, however evidence for this is weak and relevant RCTs are insufficiently powered or poorly designed. The Maxillofacial Trainee Research Collaborative (MTReC) aims to survey current antibiotic regimens in UK OMFS units treating mandibular trauma, Method: A multicentre online survey was shared via email and social media. Questions focused on current practices regarding management of mandibular fractures during pre-, peri-, and post-operative phases. Results: 89 responses from 50 UK OMFS units including 76 trainees and 4 consultants were collated over 2.5-months. 45 units routinely admitted patients; 88% clinicians starting pre-operative IV antibiotics;11 different pre-operative antibiotic regimens were identified across all surveyed clinicians, with 65% prescribing Augmentin, and remaining 35% using variable combinations of penicillins with 4 other antibiotic classifications. 5 different protocols were identified in use across the 88.8 % of respondents who chose to prescribe post-operative antibiotics. Conclusions: There is inter-unit and inter-clinician variability in prophylactic antibiotic prescription in UK patients undergoing ORIF mandibles. Given antimicrobial resistance has been declared a WHO public health threat, efforts must be made to reduce antibiotic overuse and understand regional situation specific sensitivities. The survey highlights need for nationalised protocols for antibiotics use in mandibular fractures, if at all. This survey of clinician reported practice will be used to inform a prospective observational study on 30-day outcomes of ORIF mandibles taking into account patient factors, fracture pattern, fixation type and antibiotic use.